Challenges in downstream dam passage and the effect of dam removal on Atlantic salmon (Salmo salar) smolt migrations - Shry, Samuel; Harbicht, Andrew; Forsberg, Hanna; Nilsson, Anders; Hellstroem, Gustav; Österling, Martin; Calles, Olle (Journal of Fish Biology, 2024)
Migration is critical for life-cycle completion in diadromous fish species. River connectivity is vital in facilitating these large-scale movement events, but the extent of present-day river fragmentation can interfere with these migrations. Fish passage solutions (FPSs) are commonly implemented with the aim of improving river connectivity. In our study, we investigated the performance of two types of FPSs, spill regimes and complete dam removal, on Atlantic salmon (Salmo salar) smolt migrations. We used acoustic telemetry to monitor migration behavior and passage success of 120 wild smolts released in three different groups/sites: one group with two dams to pass to reach the river mouth, a second group with one dam to pass, and a control group without any barriers to pass (upstream of a recently removed hydroelectric dam). Smolt passage probabilities were similar for the two studied dams (87% and 86%) but showed variation in path choice, delay times, and loss rates. Passage success was influenced by several factors, such as body size, diel period, and water temperature, but not flow. Cumulative passage success to the river mouth was 61%, with most individuals being lost within lentic river stretches, either in the forebays of hydroelectric power stations or in naturally wide river stretches. Within the recently rehabilitated river sections (post dam removal), passage speeds were significantly faster than all other sections of the river (post-rehabilitation x = 56.1 km/day) with significantly faster speeds compared to pre-rehabilitation (pre-x = 28.0 km/day). Our findings provide valuable information on the benefits of dam removal and highlight the need for further rehabilitation measures in upriver reaches where barriers still affect downstream passage.